Non-Canonical Mechanisms Regulating Hypoxia-Inducible Factor 1 Alpha in Cancer - Iommarini, Luisa; Porcelli, Anna Maria; Gasparre, Giuseppe; Kurelac, Ivana (Frontiers in Oncology, 2017)
Hypoxia-inducible factor 1 alpha (HIF-1α) orchestrates cellular adaptation to low oxygen and nutrient-deprived environment and drives progression to malignancy in human solid cancers. Its canonical regulation involves prolyl hydroxylases (PHDs), which in normoxia induce degradation, whereas in hypoxia allow stabilization of HIF-1α. However, in certain circumstances, HIF-1α regulation goes beyond the actual external oxygen levels and involves PHD-independent mechanisms. Here, we gather and discuss the evidence on the non-canonical HIF-1α regulation, focusing in particular on the consequences of mitochondrial respiratory complexes damage on stabilization of this pleiotropic transcription factor.